Interstitial lung disease and surfactant dysfunction as a secondary manifestation of disease: insights from lysosomal storage disorders. (2019) - Paget, Tamara L.; Parkinson-Lawrence, Emma J.; Orgeig, Sandra
Graphical abstract: Abstract : Lysosomal storage disorders are a group of genetic metabolic disorders caused by dysfunctional endosomal-lysosomal hydrolases, altered vesicular trafficking or biogenesis of the lysosome. This results in the accumulation of partially degraded substrates within cells, leading to abnormalities in multiple organ systems and reduced life expectancy. These diseases are chronic and progressive with the more severe cases experiencing the onset of disease symptoms early in life. These symptoms include skeletal, joint, airway and cardiac manifestations. Many of the lysosomal storage disorders exhibit significant respiratory issues, which frequently appear to affect pulmonary surfactant metabolism leading to an increased morbidity. Interstitial lung disease (ILD) refers to a group of disorders involving the airspaces and tissue compartments of the lung. The major categories of ILD in children that present in the neonatal period include developmental disorders, growth disorders, pulmonary surfactant dysfunction disorders, and specific conditions of unknown etiology unique to infancy. The purpose of this review is to examine the commonalities between lysosomal storage disorders with respiratory pathology and interstitial lung diseases. Increased awareness of the commonalities may instigate a more thorough investigation of symptoms thus providing an accurate and timely diagnosis enabling more precise treatment that will improve patient wellbeing.